The Effectiveness of Instructional Video as Media in Teaching Speaking Skills - Windiati Muakhiroh; Saadatuddaroini (JEET, Journal of English Education and Technology, 2024)
The quality of learning system is monotonously, and uninterested. Using media is one of tool to make students interest in learning process. Experimental design is used and the result of data analysis shows that score of pre-test 49,62 and post-test 62,85. Meanwhile, comparing mean of pretest and posttest 49,62 < 62,85. It mean, posttest score is better than pretest score and video media was more effective to improve students’ speaking skill at eighth grade of MTs. Nurul Jadid Randuboto Sidayu Gresik in the academic year of 2016/2017. And the result of interview about the difficulties in using video media to improve students’ speaking skill that there were still many difficulties using video in this research such as run ot of time, noise in the classroom, needed equipment (laptop, sound, projector) etc. Finally, the result of using video in improving students’ speaking skill is effective as interested activities, because video is a versatile and simple media for improving students’ English learning comprehension. It also made students became active to speaking.